Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/bjd.17933
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus secondary to primary biliary cholangitis: a review of the pathophysiology and management with phototherapy

Abstract: Summary Background Primary biliary cholangitis (PBC) is an autoimmune hepatobiliary disorder characterized by destruction of liver bile ducts leading to intrahepatic cholestasis. It causes intractable pruritus for which ultraviolet (UV)B phototherapy is an experimental treatment when alternative therapies fail. The pathophysiology of cholestatic itch and the mechanism of action of narrowband UVB in this condition remains poorly understood. Objectives To summarize the current literature and propose testable hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 81 publications
1
18
0
Order By: Relevance
“…The role of various factors including bile acids, opioids, steroids, and lysophosphatidic acid has been discussed, but none of them was considered as the key mediator [23]. It has been reported that elevated bile acid concentration in circulation and in the tissues during cholestasis causes itching by activating TGR5 [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The role of various factors including bile acids, opioids, steroids, and lysophosphatidic acid has been discussed, but none of them was considered as the key mediator [23]. It has been reported that elevated bile acid concentration in circulation and in the tissues during cholestasis causes itching by activating TGR5 [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…The BJD champions evidence-based dermatology. A review article included in this virtual issue considers the problem of severe, treatmentresistant pruritus associated with primary biliary cholangitis, in which destruction of liver bile ducts leads to intrahepatic cholestasis (Hussain, Samuel, Hegade, Jones, & Reynolds, 2019). Our understanding of its pathophysiology is summarized by the review, including specific receptors such as the G-protein-coupled bile acid receptor GPBAR1 and the nuclear transcription factor farnesoid X receptor.…”
mentioning
confidence: 99%
“…I was thus delighted to read the fascinating article by Hussain et al . in the current issue of the BJD in which a detailed literature review was undertaken to probe our understanding of generalized pruritus induced by cholestasis in the context of primary biliary cholangitis . A thorough evaluation of treatment approaches was also performed, with a focus on phototherapy.…”
mentioning
confidence: 99%